Reflexivity versus rigor. Issue 5 (November 2016) - Czarniawska, Barbara
Although both rigor and reflexivity are counted among scientific virtues, following these virtues in practice—whether the practice of management or the practice of research—is more complex than it might seem. In what follows, I discuss some of those complexities.